2006
DOI: 10.1099/mic.0.28682-0
|View full text |Cite
|
Sign up to set email alerts
|

A SitABCD homologue from an avian pathogenic Escherichia coli strain mediates transport of iron and manganese and resistance to hydrogen peroxide

Abstract: An operon encoding a member of the family of ATP-binding cassette (ABC) divalent metal ion transporters, homologous to Salmonella enterica SitABCD, has been identified in the avian pathogenic Escherichia coli (APEC) strain χ7122. The sitABCD genes were located on the virulence plasmid pAPEC-1, and were highly similar at the nucleotide level to the chromosomally encoded sitABCD genes present in Shigella spp. A cloned copy of sitABCD conferred increased growth upon a siderophore-deficient E. coli strain grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 53 publications
0
120
0
Order By: Relevance
“…Seven of the 31 attenuated APEC O2 mutants contained transposon insertions in genes encoding for capsule and lipopolysaccharide, indicating crucial roles of these bacterial factors in virulence (Li et al, 2005)*although direct mediation of antiphagocytic activity was not established. Apart from mediating iron and manganese transport, sitABCD operon has also been suggested to confer resistance to oxidative stress (Sabri et al, 2006) possibly required during interaction with phagocytes.…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…Seven of the 31 attenuated APEC O2 mutants contained transposon insertions in genes encoding for capsule and lipopolysaccharide, indicating crucial roles of these bacterial factors in virulence (Li et al, 2005)*although direct mediation of antiphagocytic activity was not established. Apart from mediating iron and manganese transport, sitABCD operon has also been suggested to confer resistance to oxidative stress (Sabri et al, 2006) possibly required during interaction with phagocytes.…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…In contrast, the higher frequency of sitA in commensal strains than in septicemic, and the similar frequencies of this gene among commensal and swollen head syndrome and omphalitis strains could indicate that this gene could not, per se, be related to the pathogenic mechanisms present in APEC. A recent study made by Sabri et al (2006) showed that a SitABCD homologue system found in an APEC strain does not have a potential contribution to the virulence of the strain. These authors proposed that the contribution of SitABCD to the virulence of APEC could also differ among different APEC strains or serogroups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the Sit system is required for full virulence of Salmonella Typhimurium and that a sitB mutant of APEC strain IMT5155 is markedly attenuated for survival in the chicken as demonstrated by in vivo competition assays (Janakiraman & Slauch, 2000;Li et al, 2005). Only recently, Sabri et al (2006) demonstrated that, unlike other SitABCD metal-type transporters identified in Salmonella Typhimurium and Shigella flexneri, the sitABCD operon of APEC strain x7122 is located on a virulence plasmid and not only mediates transport of iron and manganese but also is involved in oxidative stress defence of this pathogen. The sitABCD operon was also identified on large plasmids in two other APEC strains of serotypes O1 and O2 (Johnson et al, 2006b, c), and moreover IMT5155 was confirmed to harbour two copies (chromosomal and plasmid) of particular operons (unpublished data from our laboratory).…”
Section: Discussionmentioning
confidence: 99%
“…Among the wildtype-enriched spots, four were found to represent proteins involved in iron uptake (spots 1-4), indicating a notable role of YjjQ in the utilization of this metal (Table 3): SitA is a periplasmic iron-binding protein which is encoded in a four-member operon that mediates manganese and iron transport (Hantke, 2001;Sabri et al, 2006;Zhou et al, 1999). The second downregulated protein, ChuA, is involved in haem uptake in EHEC, UPEC, APEC (Li et al, 2005;Torres & Payne, 1997;Welch et al, 2002) and several other bacterial pathogens.…”
Section: Proteins Regulated By Yjjqmentioning
confidence: 99%